Desentralisasi sebagai salah satu Sub Sistem Reformasi Aministrasi - Jat Jat Wirijadinata (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2006)
Decentralization in Indonesia has been relatively influencial to the government administration system as awhole. It has also made impact both negative and positive to many aspects of the local government implementation. This article firstly describes some probles of decentralization in the religions which mainly jeopardize stability in all sectors such as economies, social, and politics. Then, it present some important variables that have to be considered to solve the problems of decentralization. The article then brings us to the concept of transforming organization which considers organization as living organiszm, concept of cost benefit analysis, cost and public service. Finally, this article is ended with the summary concluding that decentralization can improve local people’s empowerment, democracy, and quality service.